UNFOLDING THE EFFECT OF BANYUMAS VALUES AND HOME EDUTAINMENT TOWARD ANTI-FOOD WASTE LIFESTYLE AMONG YOUNG CONSUMER - Qornaeni Linda; Putri Nur Faizah; Andy Chrysanto Cahyadi; Shilfia Faradisa; Khasbi Niami; Fauzan Romadlon (Journal of Rural Development and Applied Technology, 2024)
Banyumas values are ancient traditions, and cultures are slowly considered old-fashioned and outdated. It creates a reluctance to implement, continue, and believe in them. The value is almost similar to Javanese values, but it has some differences. The value shall be maintained to mitigate food waste in this era. The National Waste Management Information System (SIPSN) of the Ministry of Environment and Forestry (KLHK) mentioned that total food waste reached 74.11% In Banyumas, and young consumers dominate the proportion of Indonesia's demographics. This research aims to find the relationship between Banyumas values, home edutainment, household routine, and anti-food waste lifestyle from young consumers. The method used was quantitative, and the statistical approach used the SEM-PLS (Structural Equation Modeling - Partial Least Square) with 409 respondents. The results showed that Banyumas values, home edutainment, and household routines significantly influence an anti-food waste lifestyle. To maintain the anti-food waste lifestyle of the young consumer in Banyumas, it needs education from their family by conducting food literacy. Young consumers shall be guided to preserve their food and avoid waste whenever they stay. Furthermore, the responsibility of each young consumer shall be maintained and revisit the cultural aspects of Banyumas as a society that upholds the local wisdom.